2021
DOI: 10.3390/nu13082704
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplements and Neuroprotective Diets and Their Potential Clinical Significance in Post-Stroke Rehabilitation

Abstract: Nutrition and rehabilitation are crucial in post-stroke recovery, especially in the elderly. Since stroke is the leading cause of long-term disability, there is a need to promote special, individually tailored nutrition strategies targeting older patients with low motor ability. Chronic stroke survivors have higher risk of developing nutrition-related chronic diseases, such as sarcopenia, anemia, type 2 diabetes mellitus and osteoporosis. Moreover, reduced motor activity, cognitive impairment and depression mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 99 publications
0
34
0
Order By: Relevance
“…Spastic myopathy should be treated with an appropriate physical treatment, using techniques such as prolonged daily self-stretch postures at high load ( 53 ), active stretching ( 94 ), short wave and ultrasound therapies ( 95 ), as it is known that botulinum toxin injections alone will not allow any long-term meaningful muscle lengthening ( 52 , 96 , 97 ). To minimize muscle damage from the acute stages, vibrations ( 98 ), stretching postures through positioning ( 99 , 100 ) and specific splinting ( 101 ), or Leucine and vitamin D ( 102 , 103 ) might also be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Spastic myopathy should be treated with an appropriate physical treatment, using techniques such as prolonged daily self-stretch postures at high load ( 53 ), active stretching ( 94 ), short wave and ultrasound therapies ( 95 ), as it is known that botulinum toxin injections alone will not allow any long-term meaningful muscle lengthening ( 52 , 96 , 97 ). To minimize muscle damage from the acute stages, vibrations ( 98 ), stretching postures through positioning ( 99 , 100 ) and specific splinting ( 101 ), or Leucine and vitamin D ( 102 , 103 ) might also be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Post-stroke patients often experience concomitant diseases associated with poor nutrition, such as anemia, diabetes, osteoporosis, and sarcopenia. This demonstrates the urgent need for customized diets for patients during rehabilitation programs [98][99][100].…”
Section: Vitamin D and Stroke Incidencementioning
confidence: 99%
“…Nutritional supplementation included amino acids and vitamins. However, few published studies have reported the onset of depression as an outcome [35]. A randomized study in 2010, with 273 stroke patients (mean age: 63 years), suggested that treatment with B-group vitamin reduced the risk of depression (HR = 0.48) during a follow-up of 7.1 ± 2.1 years [36].…”
Section: Malnutrition and Depressionmentioning
confidence: 99%
“…In contrast, depression is considered a risk factor for malnutrition among patients with stroke [35,37]. Stroke survivors with depression have less energy intake [38].…”
Section: Malnutrition and Depressionmentioning
confidence: 99%